Functionalization of reduced graphene oxide with polysulfone brushes enhance antibacterial properties and reduce human cytotoxicity. (January 2017) - Peña-Bahamonde, Janire; San Miguel, Verónica; Nguyen, Hang N.; Ozisik, Rahmi; Rodrigues, Debora F.; Cabanelas, Juan Carlos
Abstract: The present study reports two routes to modify reduced graphene oxide (rGO) nanosheets with polysulfone (PSU) brushes via nitrene chemistry. The PSU polymer is bonded to rGO at the extremity (rGO-PSU end) and at the middle of the PSU chain (rGO-PSU mid). The resulting rGO-PSU synthetic products are carefully characterized by Raman and FTIR spectroscopy, XPS, TEM, and thermogravimetric analysis, evidencing the successful grafting of PSU onto rGO surfaces. The long-term stability of these nanosheets is also determined in common solvents. The antibacterial properties of polymer-functionalized rGO against the planktonic Bacilus subtilis and Escherichia coli are also investigated. It is established that the antimicrobial properties of these nanocomposites are due to the production of reactive oxygen species. The results also demonstrate that rGO-PSU mid presents better antimicrobial properties due to shorter polymer chains, which improves the contact of the microorganisms with the graphene surface. Graphical abstract: